Transgenic Exosomes for Thymus Regeneration - Banfai, Krisztina; Garai, Kitti; Ernszt, David; Pongracz, Judit E.; Kvell, Krisztian (Frontiers in Immunology, 2019)
With senescence Wnt4 expression is down-regulated, while PPARgamma expression increases in the thymus. Together these changes allow for thymic degeneration to occur, observed as adipose involution. However, when restored, Wnt4 can efficiently counteract PPARgamma and prevent thymic senescence from developing. In addition to Wnt4, miR27b has also been reported to inhibit PPARgamma. Our goal was to evaluate the Wnt4 and miR27b levels of transgenic thymic epithelial cell (TEC) exosomes, show their regenerative potential against age-related thymic degeneration and visualize their binding and distribution both in vitro and in vivo. First, transgenic exosomes were harvested from Wnt4 over-expressing TECs and analyzed by transmission electron microscopy showing exosomes ranging 50-100 nm in size. Exosomal Wnt4 protein content was assayed by ELISA, while miR27b levels were measured by Taqman qPCR, both showing elevated levels in transgenic exosomes of Wnt4 over-expressing TECs relative to their control counterparts. Then, for functional studies steroid (Dexamethasone or DX)-induced TECs were used as cellular aging model in which DX-triggered cellular aging was efficiently prevented by transgenic exosomes. Finally, DiI-labeled exosomes were applied on mouse thymus sections and also iv-injected into mice, for in vitro binding and in vivo tracking, respectively. We have observed distinct staining patterns using DiI-labeled transgenic exosomes on sections of young and aged murine thymus samples. Moreover, in vivo injected DiI-labeled transgenic exosomes showed detectable homing to the thymus. In summary our findings prove that exosomal Wnt4 and miR27b can efficiently prevent thymic adipose involution. Our results appoint transgenic TEC exosomes as promising tools of immune rejuvenation and contribute to the characterization of the immune-modulatory effects of extracellular vesicles in the context of regenerative medicine.